Immune-mediated loss of transgene expression from virally transduced brain cells is irreversible, mediated by IFNγ, perforin, and TNFα, and due to the elimination of transduced cells - Zirger, Jeffrey M. (2012)
The adaptive immune response to viral vectors reduces vector-mediated transgene expression from the brain. It is unknown, however, whether this loss is caused by functional downregulation of transgene expression or death of transduced cells. Herein, we demonstrate that during the elimination of transgene expression, the brain becomes infiltrated with CD4 and CD8 T cells and that these T cells are necessary for transgene elimination. Further, the loss of transgene-expressing brain cells fails to occur in the absence of IFNγ, perforin, and TNFα receptor. Two methods to induce severe immune suppression in immunized animals also fail to restitute transgene expression, demonstrating the irreversibility of this process. The need for cytotoxic molecules and the irreversibility of the reduction in transgene expression suggested to us that elimination of transduced cells is responsible for the loss of transgene expression. A new experimental paradigm that discriminates between downregulation of transgene expression and the elimination of transduced cells demonstrates that transduced cells are lost from the brain upon the induction of a specific antiviral immune response. We conclude that the anti-adenoviral immune response reduces transgene expression in the brain through loss of transduced cells